Detection of urinary leishmanial antigen by latex agglutination test (KAtex) in kala-azar patients - Haque, Rashidul; Kabir, Mamun; Mondal, Dinesh; Salam, Md. Abdus (Ibn Sina Medical College, 2010)
Background: A new unique latex agglutination test (KAtex) that detects a stable, nonprotein, disease specific parasite antigen in the freshly voided urine of patients suffering from active kala-azar has been introduced by Kalon Biological Ltd. UK. This is absolutely non-invasive method of diagnosis for visceral leishmaniasis and suitable for implementation as a rapid diagnostic tool at the point of care. Objective: Diagnostic potential of KAtex was evaluated among clinically suspected kala-azar patients in an endemic zone of Bangladesh. Methodology: KAtex was done using freshly voided urine according to the manufacturer’s instructions for sixty (60) clinically suspected patients of kala-azar admitted in Rajshahi Medical College Hospital (RMCH), Bangladesh and forty (40) healthy controls during December 2005 to June 2006. Leishmania nested Polymerase Chain Reaction (Ln-PCR) using peripheral blood buffy coat was performed for all study population (100) and Ln-PCR positive cases were considered as confirmed cases of kalaazar. Results: Out of 60 clinically suspected kala-azar patients, 56 were Ln-PCR positive and 53 of 56 Ln-PCR positive cases were KAtex positive (sensitivity, 94.64%; Mantel-Haenszel Chi sq. 79.66, p= 0.0000, confidence interval [CI], >95 to 100%). None of the healthy controls was found positive by Ln-PCR but 2 of 40 were KAtex positive (specificity, 95%; confidence interval [CI], >95 to 100%). The positive and negative predictive values of KAtex were noted as 98.10% and 92.85% respectively. Conclusion: This limited prospective study suggests that KAtex is an absolutely non-invasive urinebased antigen detection test with high sensitivity and specificity and may be useful for screening active kala-azar patients, particularly suitable for field use.